Hedging the Exchange Rate Risk in International Portfolio Diversification: Currency Forwards versus Currency Options - Raimond Maurer; Shohreh Valiani (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
As past research suggest, currency exposure risk is a main source of overall risk of international diversified portfolios. Thus, controlling the currency risk is an important instrument for controlling and improving investment performance of international investments. This study examines the effectiveness of controlling the currency risk for international diversified mixed asset portfolios via different hedge tools. Several hedging strategies, using currency forwards and currency options, were evaluated and compared with each other. Therefore, the stock and bond markets of the, United Kingdom, Germany, Japan, Switzerland, and the U.S, in the time period of January 1985 till December 2002, are considered. This is done form the point of view of a German investor. Due to highly skewed return distributions of options, the application of the traditional mean-variance framework for portfolio optimization is doubtful when options are considered. To account for this problem, a mean-LPM model is employed. Currency trends are also taken into account to check for the general dependence of time trends of currency movements and the relative potential gains of risk controlling strategies.
urn:nbn:de:hebis:30-17929
Keywords: F31; G11; G15; 330; International Portfolio Diversification; Currency Hedging; FX Derivatives; Shortfall; Währungsmanagement; Hedging; Währungsderivat; Devisenoption; Portfolio-Management; International; Schätzung; Großbritannien; Schweiz; Japan; Deutschland; USA